Preparation of Bakery Products Using Coconut Flour and Glycemic Response on Normal Healthy Adults - Ramaswamy, Lalitha; Sinthuja, R. (International Coconut Community, 2013)
Bakery products are ideal foods through which nutrition can be delivered to the consumers in an acceptable form. The feasibility of incorporating coconut flour in bakery products has been studied. Four recipes namely; biscuit, wheat bread, pizza base and puff pastry were formulated using 10%, 20% and 30% levels of coconut flour by replacing the major flour of the recipe. Organoleptic evaluation of the products showed that the products were acceptable up to 30% level in biscuits, pizza base and puff pastry and up to 10% level in bread. ANOVA comparing the mean scores showed that there was significant difference in all the criteria. The digestible carbohydrate (CHO) and energy content of the coconut flour incorporated products were less than the standard ones, while the fiber content was more. Glycemic response of 30% incorporated biscuits (which was selected to be the most acceptable from among the formulated products) in normal adults was found to be lower than the standard.